The wonderful Wizard of Oz - Baum, L. Frank (Lyman Frank), 1856-1919; Denslow, W. W. (William Wallace), 1856-1915 (New York : Books of Wonder/HarperTrophy, 1987)
After a cyclone transports her to the land of Oz, Dorothy must seek out the great wizard in order to return to Kansas.
Facsimile, with afterword by Peter Glassman.
Accelerated Reader AR
Keywords: Gale, Dorothy -- (Fictitious character) -- Juvenile fiction; Oz (Imaginary place) -- Juvenile fiction; Fantasy fiction